Amphiphilic Tobramycins with Immunomodulatory Properties1. Issue 21 (1st April 2015) - Guchhait, Goutam; Altieri, Anthony; Gorityala, Balakishan; Yang, Xuan; Findlay, Brandon; Zhanel, George G.; Mookherjee, Neeloffer; Schweizer, Frank
Abstract Amphiphilic aminoglycosides (AAGs) are an emerging source of antibacterials to combat infections caused by antibiotic‐resistant bacteria. Mode‐of‐action studies indicate that AAGs predominately target bacterial membranes, thereby leading to depolarization and increased permeability. To assess whether AAGs also induce host‐directed immunomodulatory responses, we determined the AAG‐dependent induction of cytokines in macrophages in the absence or presence of lipopolysaccharide (LPS). Our results show for the first time that AAGs can boost the innate immune response, specifically the recruitment of immune cells such as neutrophils required for the resolution of infections. Moreover, AAGs can selectively control inflammatory responses induced in the presence of endotoxins to prevent septic shock. In conclusion, our study demonstrates that AAGs possess multifunctional properties that combine direct antibacterial activity with host‐directed clearance effects reminiscent of those of host‐defense peptides.